PENGARUH MODEL PROBLEM BASED LEARNING BERBASIS MEDIA KOMIK MENGENAI PEMBELAJARAN PENDIDIKAN PANCASILA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV DI SDN 1 RULUNG MULYA - Resty Setyoningsih; Ryan Dwi Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of implementing the Problem Based Learning (PBL) model on students' critical thinking skills and learning outcomes in Pancasila Education subjects in the fifth grade at SDN 1 Rulung Mulya, Natar District. This research uses a quantitative approach with a quasi-experimental method, and a pretest-posttest design with a non-equivalent control group. The research population consists of 240 fifth-grade students, with 60 students selected as a sample through simple random sampling techniques. The sample is then divided into two groups, namely the experimental group that receives treatment using the PBL model aided by comic media, and the control group that uses traditional learning methods. Data collection is conducted through observation, tests, and documentation. Data analysis is carried out using descriptive and inferential techniques. The research results show that there is a significant increase in critical thinking skills and student learning outcomes in the experimental group. The average pretest score of the experimental group was 51.17, increasing to 83.67 on the posttest. In contrast, the control group recorded an increase from 54.81 to 80.33. The hypothesis test resulted in a significance value (2-tailed) of 0.000, which is below the threshold of 0.05, thus H0 is rejected and H1 is accepted. This proves that the use of the PBL model has a significant positive effect on improving students' critical thinking skills in Civic Education learning. Keywords: Problem Based Learning 1, Media Komik 2, Kemampuan Berpikir Kritis 3.